Oral health status of sports university students in Chennai - Nagappan Nagappan; Nagaland Tirupati; Nithin Manchery Gopinath; Duraiselvi Panneer Selvam; Gayathri Ponnusamy Subramani; Gireesh Kumar Subbiah (Wolters Kluwer Medknow Publications, 2019)
Background: The field of sports in India has its renowned importance. Oral health is mirror to general health. Thus, oral assessment to sports players by a dentist is important. The commonly faced oral health problems among sports players are oral and facial trauma, leading to fracture of facial bones and teeth. Hence, it compromises the function of chewing, loss of muscle balance, and temporomandibular joint problems. The mean of facial trauma experienced by sports players in Mysuru and Chennai was 21% and 17%, respectively. Objectives: This study aimed to assess the oral health status among sports university students in India. Clinical examination was conducted using the World Health Organization's oral health pro forma in 2013. Materials and Methods: A cross-sectional descriptive study was conducted among sports university students, Melakottaiyur, Chennai. Results: A total of 94 athletes comprising 64 (68%) males and 30 (32%) females in the age group of 18-30 years, with a mean age of 24±5.04 years, were included. The mean decayed, missing, filled (Teeth) value was 2.23±3.01 and 1.87±2.62 for male and female, respectively. Around 64% of sports persons are affected with gingival inflammation, 36% with periodontal condition, and 15% with dental fluorosis. Conclusion: This study concludes that sports persons have poor gingival, dental caries, and periodontal status.